2016
DOI: 10.1371/journal.pone.0165788
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of Higher Order DNA Structures in Friedreich’s Ataxia (GAA)n Repeats by PNA or LNA Targeting

Abstract: Expansion of (GAA)n repeats in the first intron of the Frataxin gene is associated with reduced mRNA and protein levels and the development of Friedreich’s ataxia. (GAA)n expansions form non-canonical structures, including intramolecular triplex (H-DNA), and R-loops and are associated with epigenetic modifications. With the aim of interfering with higher order H-DNA (like) DNA structures within pathological (GAA)n expansions, we examined sequence-specific interaction of peptide nucleic acid (PNA) with (GAA)n r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 70 publications
(79 reference statements)
3
30
0
Order By: Relevance
“…However, the lasting effectiveness of this therapy may still be limited by ongoing somatic expansions. Perhaps this therapy will prove effective in combination with treatments designed to disrupt secondary structures[129], slow somatic expansions [81] or promote somatic contractions [130,131].…”
Section: Transcription and Fragility In Frda And Fxs: Consequences Anmentioning
confidence: 99%
“…However, the lasting effectiveness of this therapy may still be limited by ongoing somatic expansions. Perhaps this therapy will prove effective in combination with treatments designed to disrupt secondary structures[129], slow somatic expansions [81] or promote somatic contractions [130,131].…”
Section: Transcription and Fragility In Frda And Fxs: Consequences Anmentioning
confidence: 99%
“…Furthermore, we found that sequence-specific binding using repeat-specific PNA oligomers resulted in complete disruption of the triplex formed and LNA ONs showed similar results (Fig. 5 ) [ 42 ]. These findings are currently employed in FRDA patient cell lines to upregulate FXN transcription and increase the levels of mRNA and protein (manuscript in preparation).…”
Section: Oligonucleotide Targeting Of Non-b-dna Structuresmentioning
confidence: 82%
“…Furthermore, PNA binds to dsDNA and forms double- and triple-strand structures (Fig. 3 ) through Watson-Crick, Hoogsteen, or reverse-Hoogsteen base pairing [ 42 ]. PNA [ 43 ] and LNA [ 44 , 45 ] can invade dsDNA and form different PNA:DNA, and LNA:DNA, complexes, respectively (Fig.…”
Section: Chemical Modifications Of Oligonucleotidesmentioning
confidence: 99%
“…Reports have shown that PNA can both prevent and induce the formation of G-quadruplexes [ 47 ]. Bergquist et al, have demonstrated that PNA and LNA ONs can, by strand-invasion, disrupt H-DNA structures within expanded triplet-repeats, present in various diseases, such as in Friedreich’s ataxia [ 48 ]. To increase the stability of PNA- or LNA-based DNA complexes, clamp type strand-invading ONs have been developed, so called bisPNA and bisLNA, respectively.…”
Section: Introductionmentioning
confidence: 99%